Nationwide study of surgery for primary infected abdominal aortic and common iliac artery aneurysms. Issue 3 (24th January 2021) - Hosaka, A; Kumamaru, H; Takahashi, A; Azuma, N; Obara, H; Miyata, T; Obitsu, Y; Zempo, N; Miyata, H; Komori, K; ,
Abstract: Background: Primary infected aneurysms of the abdominal aorta and iliac arteries are potentially life-threatening. However, because of the rarity of the disease, its pathogenesis and optimal treatment strategy remain poorly defined. Methods: A nationwide retrospective cohort study investigated patients who underwent surgical treatment for a primary infected abdominal aortic and/or common iliac artery (CIA) aneurysm between 2011 and 2017 using a Japanese clinical registry. The study evaluated the relationships between preoperative factors and postoperative outcomes including 90-day and 3-year mortality, and persistent or recurrent aneurysm-related infection. Propensity score matching was used to compare survival between patients who underwent in situ prosthetic grafting and those who had endovascular aneurysm repair (EVAR). Results: Some 862 patients were included in the analysis. Preceding infection was identified in 30.2 per cent of the patients. The median duration of postoperative follow-up was 639 days. Cumulative overall survival rates at 30 days, 90 days, 1 year, 3 years and 5 years were 94.0, 89.7, 82.6, 74.9 and 68.5 per cent respectively. Age, preoperative shock and hypoalbuminaemia were independently associated with short-term and late mortality. Compared with open repair, EVAR was more closely associated with persistent or recurrent aneurysm-related infection (odds ratio 2.76, 95 per cent c.i. 1.67 to 4.58; P < 0.001). Propensity score-matched analyses demonstrated no significant differences between EVAR and in situ graft replacement in terms of 3-year all-cause and aorta-related mortality rates ( P = 0.093 and P =0.472 respectively). Conclusion: In patients undergoing surgical intervention for primary infected abdominal aortic and CIA aneursyms, postoperative survival rates were encouraging. Eradication of infection following EVAR appeared less likely than with open repair, but survival rates were similar in matched patients between EVAR and in situ graft replacement. Abstract : This study investigated the clinical features and surgical outcomes of primary infected abdominal aortic and common iliac artery aneurysms, and compared treatment outcomes for endovascular aneurysm repair (EVAR) with those of open graft replacement. Age, preoperative shock and hypoalbuminaemia were independently associated with short-term and late mortality. EVAR was more closely associated with persistent or recurrent aneurysm-related infection compared with open repair, whereas propensity score-matched analysis demonstrated no significant difference in 3-year mortality between EVAR and in situ graft replacement. Rates of survival and eradication of infection encouraging